Mulla's principles of Mahomedan law/by M. Hidayatullah and - Hidayatullah, M. (New Delhi, 2005)
The great attraction of the book is the ease and clarity with which the Islamic law has been outlined. One of the notable features of the book is the Introduction which gives a proper insight into the mechanics and methodology of Islamic law and traces its history and evolution and rounds off the account with a bird's eye-view of the reforms now being made and the problems attending them.
Keywords: Mahomedan law